Actual Aspects of Cadaster Relations in the Monitoring System of Land and Rural Areas - TSARENKO, Aksana A.; SCHMIDT, Irina V.; TARBAEV, Vladimir A. (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).12, 2017)
The article is devoted to topical issues of land cadastral relations in the organization of the system of lands and rural areas monitoring. It presents a new model developed by the authors of the management system of lands and rural areas monitoring in the sphere of cadastral relations. The study is based on the methods of scientific research: systemic, geoinformational and statistical method. The modern complex approach to managing monitoring measures, suggested by the authors, will favor the right development of the conception of conducting monitoring. Strategic monitoring model makes it possible to organize work at a high technological level and moreover to achieve key results avoiding many problems and mistakes. The model is expressed through an organizational and strategic scheme-model that promotes effective work management and reliable data collection. The article also examines the issues influencing the development of the whole conception of the state and political system in the field of land cadastre relations. Solutions to the problems of technological and methodological support of the formation of modern interactive databases and the application of GIS technology, developed by the authors, give an opportunity to conduct deep integrated strategic monitoring of lands and rural areas in the sphere of cadastral relations.